2014
DOI: 10.1097/nen.0000000000000107
|View full text |Cite
|
Sign up to set email alerts
|

Microglia of Prefrontal White Matter in Suicide

Abstract: Immune functions in the brain are associated with psychiatric illness and with temporary alteration of mental state. Microglia, the principal brain immunological cells, respond to changes in the internal brain milieu through a sequence of activated states, each with characteristic function and morphology. To assess a possible association of frontal white matter pathology with suicide, autopsy brain tissue samples from 11 suicide and 25 non-suicide subjects were stained for ionized calcium-binding adapter molec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
120
0
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 161 publications
(136 citation statements)
references
References 81 publications
6
120
0
2
Order By: Relevance
“…Microglia activation was found in prefrontal cortex, anterior cingulate cortex and hippocampus of depression subjects who committed suicide. 29,30) Interestingly, we also found that elevated pro-inflammatory cytokines were associated with increased numbers of reactive microglia cells in the brain, indicating that CRS exposure activated this brain innate immune cells during the pathogenesis of depression.…”
Section: Discussionmentioning
confidence: 58%
“…Microglia activation was found in prefrontal cortex, anterior cingulate cortex and hippocampus of depression subjects who committed suicide. 29,30) Interestingly, we also found that elevated pro-inflammatory cytokines were associated with increased numbers of reactive microglia cells in the brain, indicating that CRS exposure activated this brain innate immune cells during the pathogenesis of depression.…”
Section: Discussionmentioning
confidence: 58%
“…Wherein the strong expression of this protein is associated with the activated microglia and macrophages, and the low expression is generally associated with resting microglia [21][22][23].…”
Section: Discusionmentioning
confidence: 99%
“…The lisosomal protein CD68 can be used for microglial staining [21,22]. High levels of CD68 expression are associated with macrophages and activated microglia, whilst low levels of expression are associated with resting, ramified microglia [21][22][23].…”
Section: Introductionmentioning
confidence: 99%
“…Microglial activation has been observed in postmortem brains from patients with psychiatric disorders, including schizophrenia [20], mood disorders [21,22], substance abuse [23], and suicidality [24]. However, detailed mechanisms of microglia involvement in the pathogeneses of psychiatric disorders have not been elucidated.…”
Section: Sakai Et Al / Microglial Gene Expression Alterations In mentioning
confidence: 99%
“…In terms of the pathophysiology of neuropsychiatric disorders, previous studies have identified human microglial cell activation based on conventional microglia-specific markers, including major histocompatibility complex, class II, DR (HLA-DR), complement receptor type3 (CD11b, also known as integrin, alpha-M; ITGAM), ionized calcium binding adaptor molecule 1 (IBA1, also known as allograft inflammatory factor 1; AIF1), macrophage antigen CD68, (CD68, also known as macrosialin), and glucose transporter type 5 (GLUT5, also known as solute carrier family 2, member 5; SLC2A5) [20,[24][25][26], in psychiatric illnesses, which are described below. Based on these observations, theories on the neuropsychoimmunological mechanisms of neuropsychiatric disorders have been proposed, including immunological alterations that have been demonstrated in peripheral blood and cerebrospinal fluid samples from patients with psychiatric illnesses.…”
Section: Microglial Activation In Psychiatric Postmortem Brain Samplementioning
confidence: 99%